The Targeted Therapies Era Beyond the Surgical Point of View: What Spine Surgeons Should Know Before Approaching Spinal Metastases. (16th August 2019) - Cofano, Fabio; Monticelli, Matteo; Ajello, Marco; Zenga, Francesco; Marengo, Nicola; Di Perna, Giuseppe; Altieri, Roberto; Cassoni, Paola; Bertero, Luca; Melcarne, Antonio; Tartara, Fulvio; Ducati, Alessandro; et al.
In the last few years, the treatment of spinal metastases has significantly changed. This is due to the advancements in surgical technique, radiotherapy, and chemotherapy which have enriched the multidisciplinary management. Above all, the field of molecular biology of tumors is in continuous and prosperous evolution. In this review, the molecular markers and new approaches that have radically modified the chemotherapeutic strategy of the most common metastatic neoplasms will be examined together with clinical and surgical implications. The experience and skills of several different medical professionals are mandatory: an interdisciplinary oncology team represents the winning strategy in the treatment of patients with spinal metastases